DJARUM FOUNDATION BAKTI BUDAYA DALAM MENINGKATKAN KAPASITAS ALFA SHOOFA BATIK KUDUS - Fadhilah, Nurul; Khoiriyah, Nur (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2023)
PT Djarum which is called the Djarum Foundation. This researcher discusses the Djarum Bakti Budaya Foundation in improving the efforts of Alfa Shoofa Batik Kudus. Alfa Shoofa Batik Kudus is one of the batik businesses in Kudus. The discussion in this study discusses the strategy and implementation of the Djarum Foundation in enhancing the efforts of Alfa Shoofa Batik Kudus. This research uses descriptive qualitative research in the form of field research, while data collection techniques such as observation, interviews, and documents. The results showed that the Djarum Bakti Budaya Foundation was a form of concern for the cultural results of the Indonesian people. Meanwhile, Alfa Shoofa Batik Kudus is a home for the production of traditional handmade batik, hats and embroidery that is lifted and preserves the culture of Kudus. In enhancing Batik Alfa Shoofa's business, the Djarum Foundation has a strategy of (1) approving, (2) developing human resources, (3) developing promotion. The assessment stage, the assessment stage, installation of treatment, maintenance of actions, monitoring and evaluation, termination and action. Development is carried out using Direct Contacts which is carried out with business training in the form of tourism.